Parasite Cathepsin D-Like Peptidases and Their Relevance as Therapeutic Targets. Issue 9 (September 2016) - Sojka, Daniel; Hartmann, David; Bartošová-Sojková, Pavla; Dvořák, Jan
Abstract : Inhibition of aspartic cathepsin D-like peptidases (APDs) has been often discussed as an antiparasite intervention strategy. APDs have been considered as virulence factors of Trypanosoma cruzi and Leishmania spp., and have been demonstrated to have important roles in protein trafficking mechanisms of apicomplexan parasites. APDs also initiate blood digestion as components of multienzyme proteolytic complexes in malaria, platyhelminths, nematodes, and ticks. Increasing DNA and RNA sequencing data indicate that parasites express multiple APD isoenzymes of various functions that can now be specifically evaluated using new functional-genomic and biochemical tools, from which we can further assess the potential of APDs as targets for novel effective intervention strategies against parasitic diseases that still pose an alarming threat to mankind. Trends: Increasing DNA and RNA sequencing data indicate that parasites express multiple aspartic peptidases of cathepsin D type (APDs) with several functions. APDs are involved in numerous parasitic mechanisms, from protein trafficking to tissue penetration, immune evasion, and digestion of host blood proteins. APDs are a relatively small group of enzymes with a unique mechanism of activation and substrate binding, which makes them attractive drug targets.